Screening for Microalbuminuria in HIV-Positive Children in Enugu - Ezeonwu Bertilla Uzoma; Okafor Henrietta Uchenna; Ikefuna Anthony Nnaemeka; Oguonu Tagbo (International Journal of Nephrology)
Background. Human immunodeficiency virus associated nephropathy (HIVAN) is a rapidly progressive chronic renal parenchymal disease that occurs in HIV-infected individuals and manifests commonly as proteinuria, which is preceded by microalbuminuria (MA). This clinical entity is defined as a spot urine albumin of 20–200 mg/L. Objectives. To determine the prevalence of microalbuminuria in HIV positive children in UNTH, Enugu and compare it with that of HIV-negative children. Methods. A total of 154 HIV positive children aged 18 months to 14 years and 154 HIV-negative children of corresponding attributes were screened for microalbuminuria, using Micral test II strip which has a sensitivity of 90–99%. Results. No child among the groups (HIV positive and negative) had microalbuminuria. Majority (96.0%) of HIV-positive children had nonadvanced HIV disease at the time of the study (𝑃=0.00). About 77.3% were using HAART (𝑃<0.0001), the mean CD4 cell count of the subjects was 709.2±443.9 cells/mm3; while 78.0% had nonsevere immunosuppression (𝑃=0.00). Furthermore, HIV-positive children with severe immunosuppression were younger and had shorter duration of treatment. Conclusion. Microalbuminuria may not be very common in Nigerian children irrespective of their HIV status.